Android application for point to point - Vinodh, Kumar (2014)
SBS and SMRT have good public transportation in Singapore. MyTransport.SG provides search and locate nearby bus stops and get real-time bus arrival information. Google Maps Navigation provides all transport routes and direction in Singapore. So passenger has good information on routes and bus arrival information. But they have monitor Google Maps Navigation to determine their destination via smartphone with internet connection.